1998
DOI: 10.3354/dao032137
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and prevalence of Anguillicola crassus (Nematoda) in eels Anguilla anguilla of the rivers Rhine and Naab, Germany

Abstract: Over a period of 2 yr eels were collected at several sites along the river Rhine as well as from adjacent waters and examined for Anguillicola crassus in the swimbladder. Additionally eels were collected once from a site on the river Naab (Danube system). All eels were searched for both juvenile and adult stages of A. crassus, revealing prevalences of 80 % in eels from the river Rhine and 39% in eels from the river Naab. The mean intensities were 5.6 and 7.7, respectively. With respect to the prevalence and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 14 publications
8
22
0
Order By: Relevance
“…Therefore, our result suggests that transmission rates of A. crassus by paratenic hosts may be lower than by intermediate hosts in Mediterranean lagoons. This finding may not be a general trend in nematode transmission because other studies showed a positive (Thomas and Ollevier, 1992b;Lefebvre et al, 2002b;Audenaert et al, 2003) or no relationship (Würtz et al, 1998) between parasite abundance and the size of eels. Our results are consistent with those of Schabuss et al (1997) and Gargouri Ben Abdallah and Maamouri (2006), who showed a negative relationship between the two parameters.…”
Section: Salsesleucatementioning
confidence: 64%
“…Therefore, our result suggests that transmission rates of A. crassus by paratenic hosts may be lower than by intermediate hosts in Mediterranean lagoons. This finding may not be a general trend in nematode transmission because other studies showed a positive (Thomas and Ollevier, 1992b;Lefebvre et al, 2002b;Audenaert et al, 2003) or no relationship (Würtz et al, 1998) between parasite abundance and the size of eels. Our results are consistent with those of Schabuss et al (1997) and Gargouri Ben Abdallah and Maamouri (2006), who showed a negative relationship between the two parameters.…”
Section: Salsesleucatementioning
confidence: 64%
“…Maximum values of prevalence, mean intensity and mean abundance were recorded each year in early summer and, to a lesser degree, in late winter. As previously mentioned, almost all investigations have failed to detect any seasonality (Kennedy & Fitch 1990, Möller et al 1991, Thomas & Ollevier 1992, Molnár et al 1994, Würtz et al 1998. Nevertheless, the existence of seasonal peaks has already been noted (Benajiba et al 1994, Hartmann 1994, Nagasawa et al 1994.…”
Section: Discussionmentioning
confidence: 83%
“…In fact, there are still some open questions about the temporal pattern of the infection in natural waters. Fluctuations in prevalence and intensity of the infection were generally observed across time, but for many reasons, most studies have failed to detect any seasonality (Kennedy & Fitch 1990, Möller et al 1991, Thomas & Ollevier 1992, Molnár et al 1994, Würtz et al 1998. It is not known, however, to what extent temporal variation in other factors such as eel length may influence the observed parasite count.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…From the few relevant studies hitherto available, it has been suggested that the infection spread might stabilize (Van Willingen & Dekker 1989, Ashworth 1994, Würtz et al 1998, Lefebvre et al 2002b, even though the nematode possesses many attributes of a successful invasive colonizer (Kennedy & Fitch 1990).…”
Section: Anguillicolosis In European Eels Anguilla Anguillamentioning
confidence: 99%